Invisible (Tokyo Station) City of Transformation: Social Change and its Spatial Expression in Modern Japan - Beata Kowalczyk (Asian Studies, 2011)
Within the context of modernization and globalization, processes which Japan has been undergoing since Meiji era, reorganization of the urban space and appearance of new “(semi)-public” spaces, such as railway station, share certain elements in the transformation of everyday life of the Japanese society. This paper will attempt at showing main directions of changes observable in the “society in transition” through analysis of inner order of Tokyo Station, known already also as Tokyo Station City.